A perception that the feed grain basis of reduced-crude protein diets modifies the anabolic impact of insulin on the growth performance of broiler chickens - Peter H. Selle; Shemil P. Macelline; Mengzhu Z. Wang; Sonia Yun Liu (Animal Nutrition, 2025)
This inherently speculative review provides a perception that the feed grain basis of a reduced-crude protein (CP) diets modifies the anabolic impact of insulin in broiler chickens for the first 21 to 28 days post-hatch. Insulin is a powerful anabolic hormone in non-ruminant, mammalian species; however, the importance of insulin in avian species is usually dismissed because broiler chickens are held to be hyperglycaemic and resistant to insulin. However, there are indications that embryonic and young birds are in fact sensitive to insulin and resistance to insulin develops with age. The growth performance of broiler chickens offered wheat-based, reduced-CP diets is frequently inferior to corresponding diets based on maize or sorghum. This relative inferiority is declared by retarded weight gains, elevated feed conversion ratios (FCR) and negligible increases in relative abdominal fat-pad weights. However, the digestion rate of wheat starch is more rapid than that of maize and sorghum both under in vitro and in vivo conditions. This review explores the possibility that the divergent rates of starch digestion and intestinal uptakes of glucose from wheat, maize and sorghum are modifying the anabolic impacts of insulin to disadvantage wheat-based, reduced-CP diets. Insulin resistance may be modified by circulating ammonia (NH3) concentration and acid-base balance; however, reduced-CP diets can generate elevated NH3 concentration and metabolic acidosis to the detriment of insulin sensitivity. Moreover, starch concentration in reduced-CP diets are usually increased by about 25%, which would amplify any impacts of starch digestion rates on post-prandial glucose-insulin interaction. Research into this possibility is to be encouraged because it could expedite the development and acceptance of reduced-CP diets by global broiler chicken producers.